Interdigitated capacitor based frequency splitting differential microwave sensor for complete dielectric characterization of organic liquids - Shankar Das, Gouree; Buragohain, Akash; Beria, Yatish; Kalita, Partha Protim; Doloi, Trishna; Al Gburi, Ahmed Jamal Abdullah (Elsevier B.V., 2025)
This work presents an interdigitated capacitor split ring resonator based frequency splitting differential microwave sensor for complete dielectric characterization of organic liquid samples over a wide permittivity range. The proposed sensor comprises of two identical resonators excited by a common feedline and to achieve differential sensing, one of the resonators is loaded with a sample while the other is taken as the reference. Unlike other split ring resonator sensors, the proposed sensor provides a distributed high concentration of electric field around its whole perimeter thereby increasing the sensitivity. The sensor is validated in both simulation and experimentation, and we have obtained a very high normalized sensitivity of 4.66 % for the widest range of dielectric constant 1–80.4, which is among the highest reported thus far. The sensor shows a maximum error of 3.82 % in determining the complex permittivity of unknown liquids which signifies its accuracy and applicability. The proposed sensor also possesses the additional advantage of differential sensing to minimize additional measurement errors.